2020
DOI: 10.1001/jamanetworkopen.2020.2488
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Drugs Used for Adjuvant and Metastatic Therapy of Colon, Breast, and Non–Small Cell Lung Cancers

Abstract: IMPORTANCE Drugs are used in the adjuvant, metastatic, or both settings in cancer, but the rate, direction, and speed with which drugs are tested and indicated in each setting are unknown.OBJECTIVE To identify the number of unique agents that are currently category 1 or 2A per National Comprehensive Cancer Network (NCCN) guidelines in metastatic and adjuvant settings of non-small cell lung cancer (NSCLC), breast cancer, and colon cancer, as well as the mean delay between use in these 2 settings and the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Among the most used chemotherapeutic drugs, approved as first- and second-line adjuvants in CRC, are 5-FU, irinotecan (CPT-11), OXA, capecitabine, and leucovorin[ 97 , 98 ]. Depending on the CRC subtype, these drugs are also used in combination with monoclonal antibodies, such as bevacizumab or cetuximab[ 5 ].…”
Section: Role Of β-Catenin and The Tme In The Chemoresistance Of Crcmentioning
confidence: 99%
“…Among the most used chemotherapeutic drugs, approved as first- and second-line adjuvants in CRC, are 5-FU, irinotecan (CPT-11), OXA, capecitabine, and leucovorin[ 97 , 98 ]. Depending on the CRC subtype, these drugs are also used in combination with monoclonal antibodies, such as bevacizumab or cetuximab[ 5 ].…”
Section: Role Of β-Catenin and The Tme In The Chemoresistance Of Crcmentioning
confidence: 99%
“…In routine clinical practice and outside of clinical trials, these drugs are administered largely based on primary tumor biopsies in non-metastatic breast cancer. The limited success of this predominant treatment paradigm in the adjuvant-curative setting is well known and has recently been illuminated in a study by Parsons et al (2020) , which found that of 14 drugs recommended and used in the metastatic setting, only one (gefitinib in non-small cell lung cancer) was found to yield survival benefit for early-stage cancers.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Currently, only 34.8% of drugs used in the metastatic setting are endorsed for adjuvant treatment for breast cancer, colorectal cancer or non-small cell lung cancer ( Parsons et al, 2020 ). Partially explained by more rigorous criteria for drug approval and registration in early-stage disease, the observed lack in efficacy argues against a simple correlation and indicates fundamental difference in the biology of micrometastatic vs. macrometastatic disease, with the former not adequately targeted by reutilized drug application.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…This is mainly due to the emergence of CRC patients under 50 years old and the appearance of new tumors subtypes that have a refractory response to the usual therapy[ 5 ]. Currently, two of the chemotherapeutic agents approved as first and second-line palliative drugs in CRC are oxaliplatin (OXA) and irinotecan (CPT-11)[ 6 , 7 ]. However, more than half of patients with stage II/III disease who underwent surgery and were treated with these drugs relapsed and died[ 8 ].…”
Section: Introductionmentioning
confidence: 99%